Pengaruh Love of Money, Pengetahuan Perpajakan, dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Jelanti, Desi; Sari, Intan Rahma; Winingrum, Sri Putri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research was conducted to determine the influence of Love of Money, Tax Knowledge and Taxpayer Awareness on Motor Vehicle Taxpayer Compliance among Bachelor of Accounting students at Pamulang University. The number of appropriate samples in this research was 66 students between semesters 2-7 of the Accounting Study Program. This research uses primary data, namely data in the form of opinions from research subjects (respondents) using a survey by filling in the G-Form Questionnaire. The results of filling in the Questionnaire get the percentage results for each existing variable. These results reveal that Love of Money, Tax Knowledge and Taxpayer Awareness have an influence on Motor Vehicle Taxpayer Compliance.